Rancang Bangun Alat Pembengkok Kawat Metal Jig - Muhammad Yunus; Nanda Pranandita (Jurnal Mesin Nusantara, 2021)
An UMKM (micro, small and medium scale business) in the city of Pangkalpinang, Province of Kep. Bangka Belitung, with the trademark "kebajig Lure", produces metal jigs or artificial/fake bait made of metal. One of the problems in the process of making metal jigs at UMKM is bending the wire on the metal jig, because the bending process uses loop pliers which causes the wire to be made to be non-uniform (where 10 wires, below 50% of the wire deviates from tolerance) so that the stray wire must be repaired first before the metal jig molding process. In addition, the bending time of 1 piece of wire takes about 80 seconds. This study aims to accelerate the metal jig bending process and to obtain a uniform wire with a deviation of ± 0.2 mm. After conducting the survey and initial analysis, the making of tools for bending wire is the solution. In the process of making these tools, the VDI 2222 design method is used, starting from planning, conceptualizing, designing, and finally finishing. Then carried out the process of making tools and testing wire bending. The results of the experiments conducted showed that the uniformity level of the metal jig wire was around 70% and the time required in the 1-wire bending process was ± 10 seconds, with an efficiency of ± 70 seconds from the previous process. And in the metal jig molding process, the wire repaired before the molding process is only about 30%.